Repeated cocaine exposure during adolescence impairs recognition memory in early adulthood: A role for BDNF signaling in the perirhinal cortex. (June 2020) - Mottarlini, Francesca; Racagni, Giorgio; Brambilla, Paolo; Fumagalli, Fabio; Caffino, Lucia
Graphical abstract: Abstract: The perirhinal cortex (PrhC) is critical for object recognition memory; however, information regarding the molecular mechanisms underlying this type of memory following repeated exposure to drugs of abuse during adolescence is unknown. To this end, adolescent or adult rats were exposed to cocaine from postnatal day (PND) 28 to PND 42 or PND 63 to PND 77, respectively. Two weeks later, rats were subjected to the cognitive test named Novel Object Recognition (NOR) test. We found that adolescent, but not adult, cocaine exposure caused a significant impairment in the NOR test, independently from changes in the stress response system. In adolescent saline-treated rats, NOR test up-regulated BDNF and its downstream signaling whereas a downregulation of the same pathway was observed in cocaine-treated rats together with a reduction of Arc/Arg3.1 and PSD95 expression, indicating reduced pro-cognitive structural adaptations in the PrhC. Of note, cocaine-treated adult rats correctly performed in the NOR test indicating intact recognition memory mechanisms, despite a significant cocaine-induced reduction of BDNF levels in the PrhC, suggesting that recognition memory is heavily dependent on BDNF during adolescence whereas during adulthood other mechanisms come into play.